Does the Intensity of IGG4 Immunostaining Have a Correlation with the Clinical Presentation of Riedel’s Thyroiditis? - C. A. Simões; M. R. Tavares; N. M. M. Andrade; T. M. Uehara; R. A. Dedivitis; C. R. Cernea (Case Reports in Endocrinology)
Riedel’s thyroiditis (RT) represents one type of IgG4-related thyroid disease (IgG4RTD) and the diagnosis involves quantitative immunohistochemistry showing dense lymphoplasmacellular inflammatory infiltrate consisting of IgG4-positive plasma cells with storiform fibrosis and obliterative phlebitis. We report a case of RT with progressive enlargement of the anterior neck, severe dysphagia, odynophagia, and dyspnea. The patient underwent surgical decompression of the airway, protection tracheotomy, and gastrostomy for nutritional intake 6 months after first symptoms. Complete resolution occurred after surgical treatment combined with prednisolone. Immunostaining revealed IgG4-positive plasma cells 12/HPF (high-power field) and the IgG4/IgG ratio 25%, values that were disproportionate to the intensity of the patient’s symptoms. As to this case and the few cases described and analyzed in the literature, our impression is that there is no relation between the intensity of symptoms in RT with the total number of IgG4-positive plasma cells and the IgG4/IgG ratio, but more studies are needed.